2014
DOI: 10.1017/s0007114513004236
|View full text |Cite
|
Sign up to set email alerts
|

Renal molecular mechanisms underlying altered Na+handling and genesis of hypertension during adulthood in prenatally undernourished rats

Abstract: In the present study, we investigated the development of hypertension in prenatally undernourished adult rats, including the mechanisms that culminate in dysfunctions of molecular signalling in the kidney. Dams were fed a low-protein multideficient diet throughout gestation with or without a-tocopherol during lactation. The time course of hypertension development followed in male offspring was correlated with alterations in proximal tubule Na þ -ATPase activity, expression of angiotensin II (Ang II) receptors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 72 publications
3
38
1
Order By: Relevance
“…Overall, this ensemble of data, as well as others from studies with contrasting results depending on the restriction type and window [10,33,[51][52][53][54], nevertheless converges to support the idea that deficient diets -especially those containing low protein -can disrupt the physiological interactions between RAS and renal Na + handling. Here, we provide evidence that this disruption is probably due to a local increase in Ang II, which can be considered a response to compensate (inappropriately) for the reduced renal mass, to increase the Na + -associated proximal reabsorption of a reduced pool of amino acids [5] and also to restore the impaired capacity to concentrate urine [45].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Overall, this ensemble of data, as well as others from studies with contrasting results depending on the restriction type and window [10,33,[51][52][53][54], nevertheless converges to support the idea that deficient diets -especially those containing low protein -can disrupt the physiological interactions between RAS and renal Na + handling. Here, we provide evidence that this disruption is probably due to a local increase in Ang II, which can be considered a response to compensate (inappropriately) for the reduced renal mass, to increase the Na + -associated proximal reabsorption of a reduced pool of amino acids [5] and also to restore the impaired capacity to concentrate urine [45].…”
Section: Discussionsupporting
confidence: 67%
“…We recently demonstrated that chronically undernourished rats present simultaneous losartan-sensitive alterations in renal and cardiac Na + handling [5], in which upregulation of the recently cloned and purified ouabain-resistant, furosemide-inhibitable Na + -ATPase is pivotal [6,7]. This pump is considered to be the fine-tune mechanism of Na + reabsorption by proximal tubule cells [8], and its altered kinetic and regulatory properties constitute a hallmark of kidney alterations that involve deregulated local angiotensin II (Ang II) levels, inflammation and reactive oxygen species (ROS) signaling [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid peroxidation was assessed in freshly removed whole vas deferens by measuring thiobarbituric acid reactive species (Buege and Aust ) with slight method modifications (Vieira‐Filho et al. , ; Muzi‐Filho et al. ).…”
Section: Methodsmentioning
confidence: 99%
“…In a number of animal models, the offspring of mothers given poor nutrition during pregnancy exhibit pathophysiological changes similar to those observed in human diseases [12,13,14]. Some experimental and observational findings from humans and other animals indicate an association between maternal Ca intake during pregnancy and blood pressure in offspring [15,16], while others do not [17].…”
Section: Introductionmentioning
confidence: 99%